Wellbeing and Devolution Reframing the Role of Government in Scotland, Wales and Northern Ireland - Wallace, Jennifer (Wellbeing in Politics and Policy,, 2019)
"In this book, Wallace elegantly shows how committed government intervention can improve wellbeing with rigour and impact. It's an essential read for anyone concerned with the future of the UK." Julia Unwin, CBE "As someone who commissioned one of the first attempts to learn from the devolved nations I am delighted to see this publication by Jennifer Wallace. We in England need to learn a great deal more in policy areas like wellbeing where we are clearly lagging behind the other parts of the UK." Matthew Taylor, Chief Executive, RSA "In this book, Wallace offers a practical and balanced analysis of the evolution of wellbeing as a policy narrative and framework in the devolved nations of the UK. This timely contribution is relevant to anyone interested in the emergent idea of 'wellbeing' beyond our borders too." Megan Mathias, Wales Centre for Public Policy It has been over twenty years since the people of Scotland, Wales and Northern Ireland voted for devolution. Over that time, the devolved legislatures have established themselves and matured their approach to governance. At different times and for different reasons, each has put wellbeing at the heart of their approach - codifying their values and goals within wellbeing frameworks. This open access book explores, for the first time, why each set their goal as improving wellbeing and how they balance the core elements of societal wellbeing (economic, social and environmental outcomes). Do the frameworks represent a genuine attempt to think differently about how devolved government can plan and organise public services? And if so, what early indications are there of the impact is this having on people's lives? Jennifer Wallace is Head of Policy at Carnegie UK Trust where she leads the Trusts work on understanding wellbeing. She has worked in the public and voluntary sector for almost twenty years and is the author of a large number of research-based public policy reports, many of which relate to public sector reform.